2017
DOI: 10.1093/brain/aww340
|View full text |Cite
|
Sign up to set email alerts
|

18F-AV-1451 positron emission tomography in Alzheimer’s disease and progressive supranuclear palsy

Abstract: The extent to which the tau tracer [18F]AV-1451 can differentiate between tauopathies is unknown. By comparing patients with Alzheimer’s disease and progressive supranuclear palsy (PSP), Passamonti et al. show that [18F]AV-1451 displays greater specificity for Alzheimer-related tau pathology than PSP-related pathology. A machine learning algorithm correctly diagnosed 94% of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
250
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(282 citation statements)
references
References 50 publications
16
250
1
Order By: Relevance
“…In a similar vein, tau PET imaging shows specific patterns of tau tracer retention in typical and atypical variants of AD and other tauopathies (14,15,(40)(41)(42)(43). However, unlike 18 F-FDG, tau PET at the same time provides insights on underlying neuropathology, which may allow tauopathies (e.g., corticobasal degeneration or progressive supranuclear palsy) to be distinguished from non-tauopathies (e.g., multiple-system atrophy).…”
Section: Potential For Differential Diagnosismentioning
confidence: 96%
“…In a similar vein, tau PET imaging shows specific patterns of tau tracer retention in typical and atypical variants of AD and other tauopathies (14,15,(40)(41)(42)(43). However, unlike 18 F-FDG, tau PET at the same time provides insights on underlying neuropathology, which may allow tauopathies (e.g., corticobasal degeneration or progressive supranuclear palsy) to be distinguished from non-tauopathies (e.g., multiple-system atrophy).…”
Section: Potential For Differential Diagnosismentioning
confidence: 96%
“…As aforementioned, tau pathology in AD and FTLD-Tau have different biochemical and conformational properties which could contribute. Some studies have shown the ability to discriminate PSPS patients from controls and from patients with AD [26, 75, 76]; however, evidence for potential off-target binding in melanin-containing cells has been described in regions susceptible to PSP tauopathy [74] (i.e., substantia nigra, basal ganglia) which could influence interpretation. Emerging autopsy studies provide good correlation with topography of FTLD-Tau pathology post-mortem and antemortem [ 18 F]AV1451 signal [26, 77], suggesting potential utility in FTLD-Tau but further study with tissue validation for this and other tracers is needed.…”
Section: Biomarkers For Tauopathiesmentioning
confidence: 99%
“…Transmission models show minimal neuronal toxicity associated with exogenously induced tangles [14•, 15, 16, 18], and transgenic animals may show signs of degeneration prior to tau inclusion formation [24], suggesting that the toxic species of tau may be prefibrillar tau (i.e., soluble monomers, oligomers) rather than tangles themselves [25•]. It is likely that loss of tau microtubule stabilizing function contributes as well through compromised axonal transport and resultant altered cellular metabolism [26]. Other downstream mechanisms including impaired protein degradation pathways, oxidative stress, and inflammation likely contribute in the neurodegenerative process, and targeting these systems alone or in combination with tau-directed therapies may be advantageous as well.…”
Section: Introductionmentioning
confidence: 99%
“…The radioactive tracer 18 F-AV-1451 appears especially useful for the visualization of separate patterns of tau pathology distribution within the Alzheimer's disease spectrum Dronse et al, 2017), and across different tauopathies (Passamonti et al, 2017). To assess distinct pathways of Alzheimer's diseaserelated tau pathology based on 18 F-AV-1451 PET imaging data, the multivariate approach of an independent component analysis (ICA) may represent a particularly well-suited tool.…”
Section: Introductionmentioning
confidence: 99%